Follow-up of a web-based tailored intervention promoting the Mediterranean diet in Scotland - Papadaki, A.; Scott, Jane (Elsevier Ireland Ltd, 2008)
Objective: To assess the impact of a 3-month follow-up of a 6-month quasi-experimental study conducted to evaluate a web-based, tailored-feedback intervention promoting four key components of theMediterranean diet.Methods: Fifty-three (intervention) and nineteen (control) healthy females, 25–55 years, employed attwo Universities in Glasgow, Scotland, between 2003 and 2004 participated. Participants receivedtailored dietary and psychosocial feedback and Internet education, or minimal dietary feedback andgeneral healthy-eating brochures, respectively. Dietary intake using 7d-estimated food diaries and bloodlipids were assessed at baseline, 6 (post-test) and 9 months (follow-up).Results: Intention-to-treat analyses for between-group comparisons over time showed that theintervention group had increased their vegetable intake over 9 months and had more favourable levelsof HDL-cholesterol and ratio of total:HDL-cholesterol over the 9-month assessment, compared with thecontrol group. Within-group comparisons showed that, except for fruit consumption, the interventiongroup sustained their dietary improvement at 9 months, compared with baseline.Conclusion: This intervention proved successful at sustaining most of the favourable dietary and bloodlipid profile changes achieved over the 6-month intervention at the 3-month follow-up.Practice implications: This intervention can be effective in promoting a Mediterranean-style diet in worksettings.